Desarrollo de habilidades metacognitivas en estudiantes con necesidades especiales (NEE) por medio de la integración de ambientes de aprendizaje badasod en la Web - Mendoza Culmán, Lucero (Universidad Antonio Nariño, 2023)
The purpose of this research was to design and validate a web-based learning environment to foster metacognitive skills in students with special educational needs. The environment was designed to provide support for students, to set goals and organize time and resources. It also had metacognitive triggers, to monitor and control cognitive performance so that students could adjust their learning strategies according to the needs of the task. A mixed methodology with a case study design was used, with four students with mild and moderate cognitive deficits, in a B-learning course that included topics from the Social Sciences area.